2018
DOI: 10.1111/ans.14910
|View full text |Cite
|
Sign up to set email alerts
|

Validation of data submitted by the treating surgeon in the Victorian Audit of Surgical Mortality

Abstract: Background: The Victorian Audit of Surgical Mortality (VASM) seeks to peer review all deaths associated with surgical care in Victoria, Australia. The effectiveness of the VASM as an educational and quality improvement tool is dependent on the accuracy of source data it receives. We aimed to examine the accuracy and quality of source data provided by the treating surgeon for peer review, and the inter-rater concordance level between the external validator findings and the treating surgeon. Methods: Of the 629 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We sought to minimize this by reserving analysis for the highest level of seriousness rather than possibly more contentious areas of consideration and areas of concern. A Victorian study also showed good concordance between the more serious ANZASM second‐line assessments, from which it could be inferred that there would be similarly low inter‐rater variability in FLA judgements.…”
Section: Discussionmentioning
confidence: 89%
“…We sought to minimize this by reserving analysis for the highest level of seriousness rather than possibly more contentious areas of consideration and areas of concern. A Victorian study also showed good concordance between the more serious ANZASM second‐line assessments, from which it could be inferred that there would be similarly low inter‐rater variability in FLA judgements.…”
Section: Discussionmentioning
confidence: 89%
“…Gwet [24] and Shankar and Bangdiwala [28] compared some measures and showed that AC 1 has better properties than other kappa-type measures. In addition, AC 1 has been utilized in the field of medical research over the past decade [29][30][31][32][33][34][35]. However statistical inference procedures of AC 1 have not been discussed sufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Shanker and Bangdiwala compared Cohen's κ, Scott's π, Prevalence Adjusted Bias Adjusted Kappa (PABAK) [26], AC 1 and B-statistic [27], which is not a kappa-type chance-corrected measure, in the case of two raters and binary outcomes and showed that AC 1 has better properties than other kappa-type measures [28]. In addition, AC 1 has been utilized in the field of medical research over the past decade [29][30][31][32][33][34][35]. Therefore, in this study we have limited our discussion to AC 1 in the case of two raters with binary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Staff without appropriate training may not understand either the actual data they are required to input or the significance of the data. The ANZASM have been collecting surgical death data for over a decade and regularly review their own data collection, management and transcription to ensure accuracy . The process is dependent on the initial notification of death which most commonly comes from hospitals and health services.…”
Section: Discussionmentioning
confidence: 99%
“…Under‐reported death data are not uncommon in healthcare settings; however, identification of under‐reporting to a quality assurance activity raises concerns about whether all deaths are being reported by all healthcare services. The individual audits of surgical deaths regularly review their own data and results, but the quality of hospital source notification data has never been assessed.…”
Section: Introductionmentioning
confidence: 99%